Adsorption Cu2+ Metal Ion Of Pectin From “Tongka Langit” Banana’s Crust (Musa Speices Van Balbisiana) - Sutapa, I Wayan; Siahay, Victor P.D.; Tanasale, Matheis F.J.D.P. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2014)
The adsorption Cu2+ metal ion of pectin from